Ragged Lady $1 (BVolume 2s - Howells, William Dean, 1837-1920 (Salt Lake City, UT : Project Gutenberg, 2004)
"Ragged Lady $1 (BVolume 2" by William Dean Howells is a novel likely written during the late 19th century. The story continues to follow the journey of Clementina Claxon, a young woman navigating social complexities and personal relationships as she travels with Mrs. Lander in New York and then to Europe. Themes of identity, class, and societal expectations are central to the unfolding narrative as Clementina encounters various characters, revealing her innocence and the challenges of her upbringing. At the start of the book, Mrs. Lander and Clementina arrive in New York, where they are warmly welcomed back at their hotel. They engage in lively discussions about their next steps, including a potential voyage to Europe with Mrs. Milray, who shows interest in Clementina. The opening portion highlights moments of social interaction, where Mrs. Lander's opinions on other characters, including Mrs. Milray and her husband, are revealed alongside Clementina's reflections on her own place within this social setting. Questions of loyalty, the influence of social status, and the innocence of youth emerge, setting the stage for further developments in their European adventure. (This is an automatically generated summary.)s
Release date is 2004-10-24
Produced by David Widger
Keywords: Young women -- Fiction; New England -- Fiction; Americans -- Italy -- Fiction